A Bronze Worker’s Anvil and other Tools recently acquired by the Inverness Museum, with a Note on another Scottish Anvil - Childe, V Gordon (Proceedings of the Society of Antiquaries of Scotland, 1948)
A group of objects described as part of a metal-worker's stock comprising a broken spearhead, a socketed hammer and an anvil. The wider distribution of anvils is considered.